2016
DOI: 10.1007/s12603-015-0570-4
|View full text |Cite
|
Sign up to set email alerts
|

Effects of nutritional supplements on muscle mass and activities of daily living in elderly rehabilitation patients with decreased muscle mass: A randomized controlled trial

Abstract: The results of this study suggest that nutritional intervention added to resistance training during convalescent rehabilitation may improve skeletal muscle mass and activities of daily living.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
43
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 69 publications
(47 citation statements)
references
References 46 publications
4
43
0
Order By: Relevance
“…Sample size was calculated using data from our previous study . The results of that study showed that the BI score of older patients admitted to the hospital was normally distributed with a standard deviation of 19.7.…”
Section: Methodsmentioning
confidence: 99%
“…Sample size was calculated using data from our previous study . The results of that study showed that the BI score of older patients admitted to the hospital was normally distributed with a standard deviation of 19.7.…”
Section: Methodsmentioning
confidence: 99%
“…Malnutrition is associated with poorer rehabilitation outcome and physical function . Furthermore, as one of the authors reported recently, nutritional intervention might improve activities of daily living (ADL) in older rehabilitation patients . However, there is much less attention on the prevalence of poor oral status in rehabilitation settings compared with malnutrition.…”
Section: Introductionmentioning
confidence: 99%
“…The concept of "rehabilitation nutrition," a combination of both rehabilitation and nutritional care management, may improve outcomes in older disabled patients with malnutrition and sarcopenia (22). Moreover, as one of the authors reported recently, nutritional supplements may improve ADLs in older disabled patients with sarcopenia who require rehabilitation (24). This study had several limitations.…”
Section: Discussionmentioning
confidence: 87%